Population Pharmacokinetics Modeling of Vancomycin Among Chinese Infants With Normal and Augmented Renal Function - Li, De-Yi; Li, Ling; Li, Gui-Zhou; Hu, Ya-Hui; Guo, Hong-Li; Jing, Xia; Chen, Feng; Ji, Xing; Xu, Jing; Dai, Hao-Ran (Frontiers in Pediatrics, 2021)
There have been good amounts of population pharmacokinetic (PPK) models of vancomycin for Chinese pediatric patients, but none of them had a special focus on modeling infant population with different levels of renal function. Since renal function variability is prominent among infant population and the clearance (CL) of vancomycin is heavily related to renal excretion, it is important to establish precise PPK models based on individual renal function levels. We employed a PPK approach to in parallel develop three models of vancomycin for Chinese pediatric patients with normal renal function (eGFR between 30-86 mL/min/1.73 m2, model 1), with augmented renal function (eGFR ≥ 86 mL/min/1.73 m2, model 2) and with all levels of renal function (model 3). Three one-compartment models with first-order elimination were established. The predictive ability of model 1 and model 2 among each certain population are comparable to model 3 with no statistical difference. Our study revealed that among the pediatric population with augmented renal function, only body weight was included as a co-variate, which indicated that for an infant whose eGFR ≥ 86 mL/min/1.73 m2, taking blood sample is not compulsory for predicting vancomycin blood concentration, which avoids unnecessary injury to vulnerable infants.